Latitude variations of soil bacterial community diversity and composition in three typical forests of temperate, northeastern of China - Fu, Xiao-Yu; Cheng, Zhi-Chao; Ni, Hong-Wei; Zhang, Rong-Tao (Frontiers in Earth Science, 2023)
Soil bacteria are a crucial component of forest soil biodiversity and play important functions in numerous ecosystem processes. Hence, studying the variation of diversity and composition of soil bacteria between latitude gradients and the driving factors responsible for these differences is important for understanding the changes of soil bacteria. We used Illumina MiSeq sequencing of bacterial 16S rRNA to investigate the distribution pattern and driving factors of bacterial diversity and composition in temperate forest soils at three different latitudes in northeast China, with samples taken at low, middle and high latitude. Each sample area was located at a distance of 1,200 km. Our results indicate that the soil bacterial diversity decreased with increasing latitude. Members of the phyla Acidobacteria and Proteobacteria were the dominant in all investigated soils, the highest relative abundances of these phyla were: Acidobacteria and Proteobacteria in high-latitude forest, Rokubacteria and Actinobacteria in low-latitude forest. The dominant bacterial genera in the three different latitude forests were Candidatus_Solibacter, Bryobacter, Roseiarcus and Granulicella. Mean average temperature, soil pH and total nitrogen content were the key environmental factors shaping the soil bacterial diversity and composition in different latitudes of these temperate forests. The results of this study contribute to a deeper understanding and better predictions the latitudinal pattern of soil biodiversity.